Processing and storage stability of cassava (Maninot Esculenta Crantz) chips - Mejares, Carolyn Tenorio (Iloilo School of Technology, U.P. Visayas, 2003)
Cassava tubers aging 190-230 days (approximately 6-8 months after planting) with pH of 6.14 and moisture content of 77.79% were found suitable for chip making.
Sotech thesis.
Keywords: Food processing; Storage; Cassava; Manihot Esculenta Crantz